A inquisição nas Minas setecentistas: tensões constitutivas na persecução da feitiçaria - Isabela de Andrade Pena Miranda Corby (2023)
This thesis analyzes a documentary set of primary sources consisting of summaries of guilt and denunciations for witchcraft originating in the colonial territories of Minas Gerais in the period from 1700 to 1774, which are recorded in the Notebooks of the Promotor of the Inquisition of Lisbon, in addition to examining the processes related to the witchcraft in the inquisitorial jurisdiction and establish a comparison between all this documentation and the sentences for witchcraft judged in the ecclesiastical jurisdiction. The study of the sources selected during the research work starts from the problem about that there is a mismatch between the number of inquisitorial processes initiated for witchcraft – only two – and the vast amount of summaries of guilt and denunciations – eighty-nine. The analysis of these documents makes evident the existence of a constitutive tension between the inquisitorial and ecclesiastical jurisdictions in the witchcraft persecutions and, especially, between the normative expectations of the different actors involved, which are often different. This conflict relationship is expressed either in terms of procedural requirements (witnesses, complaints, evidence, etc.); regarding the way to proceed (prudence, caution, rigor, etc.); and regarding the characterization of sorcery itself in the face of concrete cases. While the Court of the Holy Office in Lisbon adopted a procedural rigor in the memory of denunciations and summaries of guilt before determining the initiation of a process, the inquisitorial agents and members of the ecclesiastic acting in the colonial territories of Minas Gerais sought to attend to the hopefuls, interests and demands from the local population, even at the expense of procedures and ways of proceeding, resulted in procedural defects that did not go unnoticed by the Prosecutor and the Board of the Inquisition.